SIS Framework for Risk Assessment Through Quantitative Analysis - Naga Malleswari, D; K.Subrahmanyam, Dr (International Journal of Engineering and Technology, 2018)
Now a days, risk management plays very important role in Information systems, currently there are various risk assessment techniques. When system is analysing the source code, automatically some disputes may arise which depends on various reasons. These disputes may arise some of the risks in information system which may leads to loss of some data. To avoid that, in this paper we are implementing a framework for source code analysis which is used for brief assessment of risk, which includes guidance to risk minimization. In this framework source based risk assessment is done through the source code analysis. In order to assess risk that arose from the source code, first we need to calculate complexity of a source code in Information System. Finally the complexity which is the result of this framework will indicates the risk intensity of the source code.Â Â
Keywords: Risk Assessment; Risk Management; Source code analysis; Effort or Performance.